2020
DOI: 10.1155/2020/9424510
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compounds Identification and Antioxidant and Calcium Oxalate Anticrystallization Activities of Punica granatum L.

Abstract: e plant Punica granatum L. has several biological activities and a great curative and preventive power against chronic diseases. For this purpose, the objective of this work is to valorize the fruit peel of this plant in the field of phytomedicine, by quantifying and identifying its bioactive compounds and by evaluating their antioxidant and anticrystallization activities against calcium oxalate. is comparative study has been carried out by hydroalcoholic extract (E.PG) and infusion (I.PG) of the plant. e quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Regarding the content of total phenols, our results were higher than those obtained by Belkacem et al 55 and Rosas-burgos et al 56 . In previous studies, Kachkoul et al 57 quantified flavonoid and flavonol contents in the hydro-ethanolic extract of pomegranate peels, and found concentrations of 36.05±2.95 mg QE/g and 7.17±0.49 mg QE/g for flavonoids and flavonols, respectively, also,Amjad and Shafighi 58 found flavonoids values of 258.127±16.19 and 359.6±13.91 mgCA/100 g dw in n-butanol and ethyl acetate extracts of pomegranate flowers, respectively. From the aforementioned results, it appears that the ethyl acetate and n-butanol fractions contained high amounts of tannins.…”
Section: Bioactive Compoundsmentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding the content of total phenols, our results were higher than those obtained by Belkacem et al 55 and Rosas-burgos et al 56 . In previous studies, Kachkoul et al 57 quantified flavonoid and flavonol contents in the hydro-ethanolic extract of pomegranate peels, and found concentrations of 36.05±2.95 mg QE/g and 7.17±0.49 mg QE/g for flavonoids and flavonols, respectively, also,Amjad and Shafighi 58 found flavonoids values of 258.127±16.19 and 359.6±13.91 mgCA/100 g dw in n-butanol and ethyl acetate extracts of pomegranate flowers, respectively. From the aforementioned results, it appears that the ethyl acetate and n-butanol fractions contained high amounts of tannins.…”
Section: Bioactive Compoundsmentioning
confidence: 91%
“…In previous works on Moroccan pomegranate peel crude extracts, they investigated the antioxidant activities by DPPH and ABTS tests and found values ranging between 42.71±0.04-65.55±0.01 and 62.15±0.01-85.32±0.08 μg/mL, in both assays respectively, 60 in addition, by using the DPPH and the reducing power assays, they found results of 60.87±0.27 and 42.17±7.46 μg/mL, respectively. 57 Besides, Pagliarulo et al 61 proved by RP-HPLC that punicalagin isomers are the most abundant ellagitannins in pomegranate peels, and Aguilar-Zárate et al 62 examined the antioxidant activity of purified punicalagin using DPPH and ABTS radicals. They found IC50: 109.53 μg/mL and 151.50 μg/mL for both assays, respectively, which are weaker than the results found in our study, this can be explained by a synergistic effect between the antioxidants.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…During the past decade, the beneficial roles of dietary plants in KSD [ [112] , [113] , [114] , [115] , [116] ] and the antilithogenic activities of various plant extracts [ [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] ] and bioactive compounds [ [126] , [127] , [128] , [129] , [130] ] have been widely investigated. Recent reviews have summarized evidence in dietary/medicinal plants and their bioactive compounds for kidney stone prevention and management [ 131 , 132 ].…”
Section: Strategies To Prevent Ksdmentioning
confidence: 99%
“…According to a recent study, two extracts of P. granatum —hydroalcoholic and infusion—exhibited high efficiency in inhibiting DPPH radical and had significant reducing power of the Fe 3+ /ferricyanide complex. The antioxidant activity of fruit peel extracts has been justified by the presence of a high level of phenolic compounds like ellagic acid and its derivatives, as identified by UPLC-PDA-MS analysis [ 138 ]. Moreover, a study carried on arils juice and peel decoction of fifteen varieties of P. granatum and has shown that the TPC and total flavonoids content (TFC) of arils juices were about 20- and 300-fold inferior to decoctions.…”
Section: Herbal Infusions Antioxidant and Anticancer Capacitiesmentioning
confidence: 99%